Transition Probabilities and Different Levels of Prominence in Segmentation. Issue 4 (30th September 2013) - Ordin, Mikhail; Nespor, Marina
Abstract : A large body of empirical research demonstrates that people exploit a wide variety of cues for the segmentation of continuous speech in artificial languages, including rhythmic properties, phrase boundary cues, and statistical regularities. However, less is known regarding how the different cues interact. In this study we addressed the question of the relative importance of lexical stress, phrasal prominence, and transitional probabilities (TP) between adjacent syllables for the segmentation of an artificial language. We explored how duration increase, pitch rise, and the combination of duration and pitch on the antepenultimate, the penultimate, and the final syllable of a three‐syllabic word affect segmentation by native speakers of Italian. Our results indicate that, if the most frequent location of stress in the participants' native language and a lengthened syllable in the artificial language do not coincide, segmentation is disrupted. If there is no conflict between the location of stress in the native language of the participant and the lengthened syllable in the artificial language, segmentation is neither impeded nor facilitated. Pitch marked the edges of the TP‐defined words in a continuous speech stream. When TPs and pitch cues are in conflict, segmentation fails; if pitch rise coincides with the edges of TP words, segmentation succeeds, but is not facilitated. Phrasal prominence comprising both pitch and duration facilitates segmentation when aligned with the word edges. Our findings show that language‐specific peculiarities of how nuclear pitch accents are realized in the native language of the listener might interact with statistical cues in the segmentation of an unfamiliar language.